Clustering of banking activities: the experience of the Frankfurt Financial Centre (Economics and region, 2024)
The article analyses scientific approaches to the organisation of cluster formations in the financial services sector and studies possibilities of adaptation of the experience of formation and development of the Frankfurt Financial Centre to the Ukrainian realities of the financial market. The main directions of scientific research of domestic and foreign scholars on the formation and functioning of financial clusters are presented. It has been determined that the main advantages of participation in cluster formations are the possibility of expanding activities, increasing innovation activity within the cluster, economies of scale and increasing productivity. The clustering of financial structures is based on geographical location and common values of the cluster members and helps to create a favourable business environment at the regional level. The quality of communication links between cluster members improves, business communication intensifies and information exchange is accelerated. The development of cluster initiatives helps to reduce the negative effects of global and local economic crises on the financial services market by combining the efforts of market participants. The study identifies the characteristics of cluster formations, based on the classical definition of the concept of “cluster” by M.E. Porter. The features of financial clusters have been identified, taking into account the specifics of their functioning. The most powerful financial clusters in Europe have been allocated according to the Global Financial Centres Index. The structure of the Frankfurt Financial Centre is analysed and the characteristics of its individual elements are presented: cluster core members; trading platform; regulatory bodies; partner clusters; and support organisations. The article establishes that the cluster approach allows to increase the efficiency of financial organisations and can be used to increase the level of social responsibility and efficiency of sustainable development of our country, its individual regions and the financial sector of Ukraine, modernisation of the national policy of strategic development and stimulation of innovation activity of financial sector organisations, effective interaction and cooperation between organisations in the financial services market, governmental organisations and representatives of the public.
Keywords: cluster; Frankfurt Financial Centre; financial organisations; agglomeration; ranking of world financial centres